Between Monarchism and Nazism: the career of General Vasily Biskupsky in exile (1919–1945) - Vydra, Zbyněk; Jiránek, Tomáš (My University, 2024)
The article examines General Vasily Viktorovich Biskupsky’s (1878–1945) career in exile. Biskupsky emigrated from Russia in 1919, and he permanently settled in Germany. As a radical right-wing monarchist, he aimed to create connections between Russian emigrants, German far-right circles, and German conservative monarchists. His ultimate goal was to build a coalition of conservative and far-right forces, restore the monarchy in Russia, and strengthen the Russian-German alliance. However, due to his questionable contacts and suspected involvement in various affairs, such as the Kapp Putsch in 1920 and the Munich Putsch in 1923, Biskupsky acquired a negative reputation. He played a significant role in the monarchist-legitimist movement centred around Grand Duke Kirill Vladimirovich Romanov. After 1933, Biskupsky collaborated closely with the Nazi regime, seeing them as the best ally for his political plans. The article provides the first biographical sketch of Biskupsky’s life in English.
Mezi monarchismem a nacismem: exilová kariéra generála Vasilije Biskupského (1919-1945)
Keywords: Vasily V. Biskupsky (1878–1945); White Emigration; Russian Radical Right; Russo-German Relations; 1919–1945; Vasilij V. Biskupskij (1878-1945); Bílá emigrace; ruská radikální pravice; rusko-německé vzthy; 1919-1945